One World of Welfare : Japan in Comparative Perspective - Kasza, Gregory James (Book collections on Project MUSE., 2006)
"One World of Welfare offers a systematic, comparative examination of Japan's welfare policies and a critical assessment of previous research. Gregory J. Kasza rejects the view that the Japanese welfare system is unique; he challenges the nearly universal belief that the postwar Japanese state neglected welfare to promote rapid economic growth; he rejects the claim that there is a regional welfare model in East Asia; and he uses the Japanese case to question the dominant framework for comparative welfare research. The author explores the relevance of both convergence and divergence theories for understanding the Japanese record and spotlights the importance of international influences on the timing and content of Japan's welfare policies."--Jacket